Violence victimisation and young adult cardiometabolic health: the role of timing and social identity - Stephanie M. Koning; Jacob Aronoff; Shanting Chen; Taylor Hargrove; Jessica Polos; Thomas W. McDade (Annals of Human Biology)
Background Adolescent violence victimisation is associated with a spectrum of adult social and behavioural health outcomes, including adverse mental health symptoms. However, underlying social stress mechanisms linking adolescent victimisation to adult cardiometabolic health remains poorly understood.Aim The current study aims to reveal how adolescent and adult interpersonal violence exposures each get “under the skin” to affect adult metabolic syndrome, including direct victimisation and, additionally, witnessing violence.Subjects and methods We use a nationally representative longitudinal cohort, the National Longitudinal Study of Adolescent to Adult Health, and leverage a quasi-experimental approach, propensity score matching regression analysis (n = 14,267).Results We find that adolescent violence exposure carries an enduring effect on young adult metabolic syndrome risk factor incidence and high-risk status, which is independent of young adult violence. Violence effects do not vary by sex or racial identity.Conclusion In sum, adolescent exposure to direct interpersonal violence significantly affects young adult cardiometabolic health in ways suggesting adolescence is a sensitive period for the onset of harmful cardiometabolic effects in early adulthood. Findings warrant future study of underlying pathways and how these effects shape social inequities in cardiometabolic health among U.S. adults broadly.